Perbandingan Performansi Pengamanan File Backup LPSE Menggunakan Algoritma DES Dan AES - Darma Udayana, I Putu Agus Eka; Sastra, Nyoman Putra (Jurnal Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2016.v15i01p19, 2016)
LPSE is a unit established for the purpose of organizing care systems procurement of goods and services electronically to facilitate the scope of work ULP. In the main server LPSE contained important data procurement of goods / services. To maintain the availability of data every transaction and supporting the availability of the system, then the backup server devices are provided. In a process that requires data backup from the primary server to the backup server through a LAN network. In the process of data transfer required a method of ensuring the security of data is maintained. Data security encryption mechanism and descriptions used are DES and AES algorithms. Because of this encryption process, the necessary computing will indirectly membenani server. From the test results, the performance of the backup file on the server security LPSE the AES method is superior to DES method with an average time of 195.4 seconds file encryption 189.1 seconds ahead of DES method. The file size of the generated encryption is also not much different that makes the time required in the backup process is not much different. With less time required in the process of securing, then the server load will be less. DOI: 10.24843/MITE.1501.19
Keywords: Enkripsi, Deskripsi, DES, AES